Quality Attributes of Therapeutic Tea from Indian Herbs Sweetened with Stevia (Stevia rebaudiana) - Akhilesh Verma; Alpana Singh (Journal of Pharmacy and Nutrition Sciences, 2013)
Eating healthy food is vital for wellness and prevention of disease. Teas are aqueous extractions of crude herbs and one of the most commonly used delivery system for natural health products. Stevia (Stevia rebaudiana) is a sweet herb having sweetness 200 to 300 times more than sugar with zero calorific value. Therapeutically stevia is antibacterial, antifungal, anti inflammatory, antimicrobial, antiviral, antiyeast, prevents cavities, cardio tonic, diuretic, hypoglycemic, hypotensive tonic and vasodilator. Hence, sensorily acceptable therapeutic tea sweetened with stevia was formulated, optimized and assessed for various quality parameters. Therapeutic tea was optimized at 10.25% stevia leaves, 7.28% nutmeg, 32.06% arjuna bark, 5.55% licorice and 6.41% of each of ginger, cinnamon, black pepper, fennel, nagarmotha and cardamom. It is recommended that 2.34 g of tea formulation is appropriate to make 100 ml of tea infusion. Herbal tea formulations contained 8.22-9.32% protein, 18.66-18.70% ash, 42.0-45.28% carbohydrates, 72.07-82.25 mg P, 268.25-271.62 mg Ca, 80.30-83.87 mg Mg, 12.8-13.65 mg Fe, 1.82-2.60 mg Cu, 1.37-1.57 mg Zn, 3.28-3.76 mg Mn and 15.84-19.80 mg ascorbic acid per 100 g of tea mix. Bright, sparkling and clear infusion of brown colour with pleasant aroma and taste was obtained from optimized therapeutic tea formulation which would be an alternative medicine for different therapeutic purposes with minimal calories. Microbial quality of the product packed in aluminium foil bag was well up to 3 months storage at ambient temperature.